NON PERFORMING LOAN SEBAGAI PEMODERASI PENGARUH KREDIT YANG DISALURKAN PADA PROFITABILITAS - Utami, Ida Ayu Tri Istri; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect on the profitability of loans and NPL influence on the relationship between lending profitability. This research was conducted at the banks listed on the Indonesia Stock Exchange (BEI) 2012-2014. Samples was determined using purposive sampling technique. The samples selected were 30 banks with the observation period of three years so that the sample size of 90 observations. Data analysis method used is Moderated Regression Analysis (MRA). Research results prove that lending a positive effect on profitability, while NPL negative influence on the relationship between loans extended to profitability.
Keywords: Loans Disbursed, Profitability, and Non Performing Loan